PHILOSOPHICAL FUNDATIONS OF UMBERTO ECO NOVEL «TNE NAME OF THE ROSE» - Oksak , Gleb (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article examines some aspects of linguistic philosophy, which Umberto Eco was a supporter of, namely, the conventional aspect of word formation and word usage, aspects of isotropy, the problem of intertextuality of an artistic work, the philosophical principles of writing the famous novel «The Name of the Rose»; as well as the possibilities of creating author's metaphors and stylistic tropes in the creation of an artistic text.__________References:• Ponоmarіv, O. D. Kul'tura slova. Movnostilіstichnі poradi (Kiїv: Libіd' 2011), 272.• Navarenko, І. A. «Rol' avtora u tvorennі znachennja tekstu (na materіalі suchasnih hudozhnіh іspanomovnih tekstіv).» Problemi semantіki slova, rechennja ta tekstu 38 (2017): 126–128.• Eko, U. «Zametki na poljah «Imeni rozy».» (Symposium, 2002), 91.• Eco, U. Postille al nome della rosa (Milano, Bompiami, 1984).
Keywords: conventional aspect of word formation, isotopy, double isotopy, semantics, text, linguistic philosophy